PENGARUH PENERAPAN BI 7 - DAY REPO RATE, INFLASI TERHADAP STABILITAS KURS JISDOR JANUARI 2019 - OKTOBER 2021 - RIZKIA ZAHRA; ZAHRINA GHAISANY PULUNGAN; NURUL JANNAH (LP2MTBM MAKARIOZ, 2021)
The purpose of the study was to analyze the effect of the bi 7 day reverse rate and inflation on the average value of jisdorexchange rate during the time period January 2019-October 2021. The data used by this study is a type of secondary data.The analysis method used is a quantitative method based on existing data. The analysis was conducted using the SPSS 16data processing application. The variables are X1 which is BI7DRR, Variable X2 Inflation Value, and Variable Y1 is theaverage value of Jisdor January 2019-October 2021. Based on the test t the significant value obtained for variable X1 is>0.05 and the value t calculates < t of the table. Then there is no effect of variable X1 (BI7DRR) on Variable Y (JisdorExchange Rate Average). Significant value obtained for variable X2 is >0.05 and the value of t calculates < t table. So thereis no effect of variable X2 (Inflation) on Variable Y (Average Jisdor Exchange Rate). Based on the test f the significancevalue for the variable BI7DRR and Inflation simultaneously against the average Jisdor Exchange Rate is 0.309>0.05 and thevalue F calculates <F.The table can be concluded that there is no effect of the percentage of BI7DRR and Inflation on theAverage Value of Jisdor Exchange Rate in the period January 2019-October 2021. Based on the Multiple Linear RegressionAnalysis, the percentage of BI7DRR has a negative relationship with the Jisdor exchange rate value. This means that everyincrease in BI7DRR percentage of 1% then the Average Jisdor Exchange Rate will decrease by Rp.128,705. The percentageof inflation has a positive relationship with the value of jisdor exchange rate. This means that every increase in inflationpercentage of 1% then the Average Jisdor Exchange Rate will increase by Rp.33,247.